Novel Synthesis of Some Acetoxy Aryl Pyrazolines - R. Dubey, Rashmi; Dhawas, A.K.; Thakare, S.S. (Asian Journal of Chemistry, 2010)
The chalcones (IIIa-f) 1-(2'-acetoxy-3'-substituted-5'-chloro-6'-methyl phenyl)-3-(4"-substituted) aryl prop-2-enones were synthesized by the reaction of ketones with different aromatic aldehydes. These chalcones on reaction with hydrazine hydrate and phenyl hydrazine in catalytic amount of ethanol undergo cyclization to form 1- substituted- 3- (2'-acetoxy-3'-substituted-5'-chloro-6'-methyl phenyl)-5-(4"-substituted phenyl)pyrazolines. All the synthsized compounds were characterized by IR, 1H NMR data and elemental analysis.